Ideological Attacks are Taking Place in the Minds and Hearts of Young People Today Through the Internet - Худойбергенова П.Т. (Scholars Digest Publishing, 2023)
Today, the whole world uses the Internet. However, some countries are using it to create internal conflicts in other countries, create economic crises, and promote "popular culture" to young people in order to achieve their goals. Our goal is to protect young people from these attacks.
Keywords: Internet, youth consciousness, public propaganda.